دور الإعلام الرقمي في التوعية بمخاطر السباحة دراسة تحليلية لصفحة الإنقاذ البحري طلميثة على فيسبوك (Comprehensive Journal of Science, 2025)
This study aims to analyze the role of digital media in raising awareness of swimming-related risks by examining the content of the “Marine Rescue Tolmeitha” Facebook page during the summer of 2025. The findings revealed that the page placed greater emphasis on visual warning posts, which generated higher levels of audience engagement compared to informational news posts. The study concluded that digital media represents an effective tool for promoting maritime safety awareness when employed within a clear and well-defined communication strategy. It also recommended supporting digital initiatives and strengthening cooperation between rescue teams and media organizations.